Performance of VIX Option Price Models - Wang, Yang (2012)
This dissertation discusses price performance of volatility price models, Grunbichler and Longstaff (1996) mean-reverting model and Whaley (1993) model are compared in this dissertation. This dissertation involves valuation models’ details, properties of VIX and VIX option in detail and comparison with empirical results. Key Words: volatility option, volatility index, mean-reverting, non-central chi-square distribution, the gamma distribution, GARCH model.